Disaster Preparedness amongst Schools Teachers: A Holistic Approach towards Development of a Research Tool - Shahid, Shahid Iqbal; Dr Sarwat, Sarwat Nauman (Community Development Journal, 2024)
The Comprehensive School Safety Framework (CSSF) is a complete strategy for creating safe learning environments for administrators, teachers, students, and school staff. The CSS framework has three pillars: safe learning facilities, school disaster management, and risk reduction and resilience education. This study was conducted to develop a research tool to assess disaster preparedness among school teachers using the Comprehensive School Safety Framework (CSSF). A questionnaire was developed by the researcher, which had 27 items. There were 320 school teachers selected from 64 schools. On the basis of factor analysis, there were seven factors found for the disaster preparedness of school teachers: online learning and emergency preparedness, local risk awareness, physical safety and infrastructure, organization disaster management, online teaching readiness, active learning and disaster training, general awareness, and immediate response. The tool developed by the research was named disaster preparedness and risk reduction (DPRR). This tool is validated and reliable on the basis of factor analysis for the assessment of disaster preparedness amongst school teachers.